Nutrient Recovery from Palm Oil Mill Effluent for Fertilizer Production: Technology Options and Practical Barriers - Agung Kurnia Yahya; Apsari Puspita Aini; Miftahurrahmah; Anang Baharuddin Sahaq (Universitas Negeri Semarang, 2026)
Palm oil mill effluent (POME) is a high-strength agro-industrial wastewater whose management governs both environmental performance and operational resilience of palm oil mills. Treatment trains optimized solely for COD/BOD reduction often accumulate operational penalties under feed variability, including scaling, sludge burden, and persistent polishing demands, rather than forming a controllable value-generating platform. This review reframes nutrient recovery from POME as a fertilizer manufacturing problem embedded in a wastewater system, where removal does not equal recovery unless nutrients are transferred into a defined product phase with mass-balanced yield, controlled composition, impurity management, and agronomic function. Anaerobic digestion is positioned as a pivotal pivot point because it converts organic load to methane while producing an anaerobically digested liquor that is operationally more suitable for targeted nutrient recovery than raw POME. Using a PRISMA-ScR scoping review with a systematic search, evidence was mapped across three coupled outcome domains: water reuse/reclamation, energy recovery (biogas/CH₄), and nutrient circularity (N–P recovery and derived products). The synthesis compares unit operations by function and operability constraints, then assembles feasible combinations into a process superstructure and a decision roadmap for pathway selection under mill constraints. Findings emphasize that raw POME and anaerobically digested POME are not interchangeable feedstocks: raw POME is dominated by solids/colloids that hinder selective recovery and contaminate products, while post-digestion variability is more chemistry-driven and governs precipitation windows and membrane stability. Recovery options converge toward hybrid systems integrating crystallization (struvite/phosphate minerals), adsorption/ion exchange with regenerability, membrane concentration including fertilizer-drawn forward osmosis, and biological assimilation (microalgae), with fouling, scaling, and crystallization inhibition as decisive design variables. Overall, meaningful nutrient recovery from POME is achieved only when fertilizer grade products are produced while simultaneously reducing compliance risk and operational burden.